A Brief History Of A Smelting Company With Reference To The History Of Malaysian Tin Industry 1869 - 1966 - Yunus, Junian Haji (Universiti Sains Malaysia, 1974)
Our research was mainly concentrate at the company office at 73, Dato Keramat Road, Penang. The necessary secondary background was done at the university’s Library at the Minden and also at the company’s Library.